2015
DOI: 10.1007/s10151-015-1394-2
|View full text |Cite
|
Sign up to set email alerts
|

A theory of progression from obstructed defecation to fecal incontinence

Abstract: Fecal disorders have a relevant social impact because they impair the quality of life of the patient and add to the cost of healthcare. In order to shed light on the pathophysiology of fecal disorders it is helpful to consider the progression of obstructed defecation to fecal incontinence which occurs in women without anal sphincter defects who have descending perineum syndrome.The overall prevalence of chronic constipation in the general population is about 15 %, and the most common subtype among women is obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…This nding indicates that awareness of the problem among the general population by general practitioners and medical specialists should be increased to encourage individuals to seek help, so that physicians can offer timely and adequate treatment. It is known that untreated dyssynergic defecation and mild constipation can progress to severe constipation, which can lead to irreversible alterations of the pelvic oor, such as pudendal neuropathy, and fecal incontinence over the course of time [31].…”
Section: Discussionmentioning
confidence: 99%
“…This nding indicates that awareness of the problem among the general population by general practitioners and medical specialists should be increased to encourage individuals to seek help, so that physicians can offer timely and adequate treatment. It is known that untreated dyssynergic defecation and mild constipation can progress to severe constipation, which can lead to irreversible alterations of the pelvic oor, such as pudendal neuropathy, and fecal incontinence over the course of time [31].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently this small amount of stool may leak out of the anus unconsciously, because of the impairment of conscious contraction of the anal sphincter. 21 The FIS is commonly used to assess the continence. Our study demonstrated a significant reduction (38.37%) in FIS score in patients of constipation with ODS after therapy with combination laxative therapy which could be attributed to the overall improvement in straining, consistency and frequency of defecation.…”
Section: Discussionmentioning
confidence: 99%
“…This may include passive faecal leakage or urge incontinence, and the coexistence of symptoms is missed by over 85% of referring clinicians [8]. In fact, the progression of longstanding obstructed defaecation to faecal incontinence is widely acknowledged, and an area of ongoing longitudinal research-these patients often have signs of mechanical dysfunction including perineal descent [9], presumably from excessive straining over years.…”
Section: The Symptom Complex and Associated Problemsmentioning
confidence: 99%